Strategi Pemberdayaan Masyarakat Melalui Pengembangan Kapasitas Kelembagaan Kampung Adat di Kabupaten Siak Provinsi Riau - Raja Amin; Isril; Rury Febrina (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2016)
This paper will examine the strategies to empower the Kampung Adat community through the development of institutional capacity in The Regency of Siak. The Regency of Siak is one of the districts that have established Desa Adat territory. Based on the Siak District Regulation No.02/2015 specifies eight Kampung Adat located in the district of Siak. Regulation for Kampung Adat setting in Siak district has gone through a long process started from; First, the opportunities of formation the Kampung Adat after the issuance of Law No. 6 2014 about the village. Secondly, the formation of team to determine and the establishment of Kampung Adat. Third are socializing, inventarization, identification and assessment as well as recommendations from the Regent. Fourth is the release of regulation of Kampung Adat in Siak district, Fifth is getting the Registration Number from the Provinces and Sixth is getting Kampung Adat Registration Code from Ministry of Internal Affair. But there is a hiatus periode on the process of determination of Kampung Adat in Siak district due to several things, such as yet issuance of Kampung Adat Code from the Ministry of Internal Affairs, the lack of regulation related provincial level Structuring the Kampung Adat, and the lack decree as technical guidelines for the process of reviving traditional village. Siak district government through BPMPD address this hiatus conditions with suggestion to the administration of the Kampung Adat and Adat leaders in particular to immediately arranged a draft form of village institutions or Adat regulations until provincial regulations and codes of Kampung Adat officialy released. This strategy is to accelerate the progress of forming the institution of Kampung Adat and to avoid longer hiatus on establishment. Strategy of community empowerment through the development of institutional capacity both government institutions, community organizations and traditional institutions have been prepared by the Government of Siak, it can be seen from the activities that are directed to the strengthening of the institutional capacity of government Kampung such as: capacity building for the selected Penghulu, The chairman LPMK and Chairman BAPEKAM for periode 2015- 2021, Bimtek government, kasi PMD districts and porters for all Siak Region, as well as coaching the village headman, the head of customary, traditional institutions chairman and chief BAPEKAM for all Siak Region. But then again BPMPD is not yet specifically arrange the activities to directly relate to the Kampung Adat because of the code for Kampung Adat is not yet obtained. At the level of Village Institution has also drawn up a planning document for development and have incorporated programs related to community development and empowerment, but still using the previous nomenclature which is Village.